Kajian besaran angkutan sedimen pada Sungai Larona Kab. Luwu Timur dengan menggunakan beberapa metode empiris - Syarif, Muhammad Yusuf; Musa, Ratna; Mallombassi, Ali (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In 2023, the Larona River in Pongkeru Village overflowed, inundating several residents' houses. One of the factors causing this was the shallowing of the river due to sedimentation in the Larona River. The river flow also transported sediment materials from the erosion process carried by the water flow. This study aims to determine the estimated rate of bottom sediment transport using the Einstein and Mayer Peter Muller methods on the Larona River located in Pongkeru Village, Malili District, East Luwu Regency, South Sulawesi Province using the Einstein and Mayer Peter Muller equations. This study uses a quantitative research method with sediment as the dependent variable, river depth (h), river width (L) as independent variables. The results of this study indicate that the volume of sediment rate of the Larona River using the Einstein Method was obtained at 1,338 m3/day under normal conditions and 1,729 m3/day under flood conditions, for the Meyer Peter Muller method it was obtained at 7,391 m3/day under normal conditions and 18,741 m3/day under flood conditions.